Facile fabrication, morphology control, and modification of polymeric yolk–shell microspheres. (13th September 2018) - Han, Yingying; Pan, Mingwang; Yuan, Jinfeng; Mei, Shuxing; Zhu, Lei; Liu, Gang; Yu, Haifeng
Abstract: The fabrication and functionalization of polymeric yolk–shell microspheres (YSMs), possessing a hollow shell and a movable core, is interesting but challenging in materials science. Here we report the facile fabrication, morphology control, and fluorescent modification of polymeric YSMs, which have a spherical core of poly(vinylidene fluoride) (PVDF) and a hollow shell of poly(styrene-co-glycidyl methacrylate). First, flower-like microspheres with core–shell structures are synthesized via seeded surface nucleation in an emulsion polymerization of styrene, glycidyl methacrylate, and divinylbenzene by using PVDF microparticles as seeds. Both the feed ratio and the polymerization time are considered to manipulate the core–shell structures of the composite microparticles, which obviously influences the morphology of the YSMs obtained from the subsequent treatment of solvent etching to remove the seed. The hollow volume of the polymeric YSMs is easily adjusted by changing the etching time at different temperatures. Meanwhile, we realized three-dimensionally confined crystallization of PVDF in different morphologies of YSMs. Furthermore, YSMs with the same or different functional groups, inside and outside of the hollow shell, respectively, are chemically modified by the reaction of glycidyl groups on the shell with 2, 2′-(ethylenedioxy) bis-ethylamine. Thus, strong fluorescence of the YSMs is observed by subsequent labeling with functional fluorescent groups.